Characterization of shade-grown coffee production in Totonac communities in the Northeastern Sierra of the state of Puebla, Mexico (Agro Productividad, 2026)
Objective: to characterize the production of shade-grown coffee (Coffea arabica L.) in Huehuetla, Ixtepec and Zongozotla, municipalities with Totonac population in Sierra Nororiental, Puebla, Mexico.Design/ Methodology/ Approach: this study was conducted from January to June 2024. To collect data, 93 semi-structured interviews were conducted, consisting of three types of records; 1: general data, 2: socioeconomic and productive aspects; and 3: agronomic management. Among the surveyed participants, 69% were men and 31% were women.Results: in these municipalities, 12 varieties of coffee are grown, associated with 50 plant species, 16 of which are used for shade. Coffee growers identified coffee rust (Hemileia vastatrix) as the main disease, and the coffee-berry borer (Hypothenemus hampei) as the primary pest. The yield of parchment coffee in this region is lower than the average in the state of Puebla (460 kg ha-1). The most common practices identified are weed control, pruning of coffee plants, shade management, and soil fertilization.Limitations/ Implications of the study: foliar fertilization, application of insecticides and fungicides are implemented to a lesser extent; which suggest that coffee growers require attention and related training.Findings/ Conclusions: based on the results obtained, we suggest that agricultural activities be increased; while promoting the coffee sector through government agencies. Management plans should be designed in a way that, in addition to considering the biological requirements of coffee cultivation, they also incorporate the socioeconomic and cultural contexts.